Disaster Risk On Review Scale And Spatial Planning Archipelago Region: The Risk Based Island Cluster In Moluccas Province - Ferad Puturuhu; Restia Christianty (Universitas Negeri Gorontalo, 2020)
Disaster risk reduction (DRR) by taking into account the spatial planning in its implementation is not easy, for the Moluccas which has the characteristics of the region that has many cluster islands, and the accessibility are still low. Thus it requires special handling in the island-based disaster risk reduction, which will certainly be different from disaster risk reduction efforts that were undertaken in the continental region. The purpose of this research is to design the spatial area of the island cluster in Moluccas Province based on disaster risk. The method used is literature through spatial analysis of island risk-based groups. Based on the results of disaster risk assessment by the BPBD of Moluccas Province, it has been obtained that there are islands based on disaster risk (RB-islands cluster). The high disaster risk level was the island cluster on RB III and IX, the medium disaster risk level was the island cluster on RB I, IV, VI, and VIII, the low disaster risk level was the island cluster on RB II, V, and VII. The RB island cluster is a model for reaching areas with high disaster risk, can easily identify what causes it. It become an input to mitigate it through the spatial arrangements for achieving a sustainable archipelago development. The regional spatial arrangements aimed at reducing disaster risk in the RB-islands cluster in the Moluccas through spatial planning, structural handling/civil engineering, education, and community empowerment.